Pengembangan Model Evaluasi Pendidikan Karakter Dalam Pembelajaran di Sekolah - Imas Masruroh (Jurnal Ilmiah Wahana Pendidikan, 2022)
It is necessary to revive the values ​​of etiquette and good character among students, the loss of good character is much influenced by environmental factors, both society and the educational environment. This study uses a qualitative research approach using descriptive analysis methods that use literature study analysis techniques (Library Research). The results of the study show the evaluation of character education as a benchmark for achieving the development of character education in schools. School is the second best environment after the family environment in the process of character education. Educational institutions have measurable educational programs and systems due to a continuous pattern of character education between character education and other subjects.